Aphrodisiac Effect of Ethanol Extract of Piliostigma thonningii Leaf on Male Albino Wistar Rats - Dasofunjo K; Asuk A.A; Ezugwu H.C; Nwodo O.F.C.,Olatunji T.L (Journal of Applied Pharmaceutical Science, 2013)
In an attempt to evaluate the acclaimed aphrodisiac activity of ethanol leaf extract of Piliostigma thoningii, twenty (20) male wistar albino rats were weighed and grouped into four study groups (A-D) of five animals each. Rats in group A (control) were administered with 1ml of distilled water orally while those in groups B, C, and D were given same volume orally, corresponding to 50, 100, and 200 mg/kg body weight of the extract respectively for 21 days. Sexual behaviour parameters were monitored in the male rats for 3 days after administration by pairing with a receptive female (1:1). The male serum testosterone concentration was also determined. Cage side observation on the animals revealed prospective behaviours by the receptive female rats and pre- copulatory behaviours by the extract-treated male rats. The extract at 50, 100, and 200 mg/kg body weight significantly (P < 0.05) increased the frequencies of mount and intromission. In addition, the ejaculation latency was significantly (P < 0.05) prolonged. The latencies of mount and intromission were reduced signifi-cantly (P
Keywords: Aphrodisiac, sexual behaviour, antioxidant, antimicrobial and anti-nutrients.